Development of pharmaceutical care tools for people living with HIV treated at a medium- and high-complexity hospital (Research, Society and Development, 2022)
The exposure of people living with HIV (PLHIV) to antiretrovirals (ARV) can cause significant adverse effects, contributing to their low adherence to treatment. The pharmacist can contribute to the optimization of PLHIV drug therapy through pharmacotherapeutic monitoring, favoring adherence to ARV therapy and, consequently, suppression of the viral load. The objective of the present study was to develop a pharmacotherapeutic monitoring routine for PLHIV in outpatient follow-up at a medium- and high-complexity hospital in the city of Rio de Janeiro. This is an experimental development project that consists of using knowledge from practical experience and research from the specialized literature to subsidize the structuring of a new service to support PLHIV. The work was divided into three parts: development of the necessary instruments for pharmaceutical care, elaboration of standard operating procedures (SOPs) for patient care, and testing of routines and work tools. The educational leaflets for patients and information boards were developed through a literature search, whereas the pharmaceutical documentation instruments and SOP were developed through adaptations of the Dáder Method. All work instruments were subjected to a test to evaluate the need for changes to improve the service.